PENGEMBANGAN EKONOMI PRODUKTIF BAGI KELOMPOK TANI PEMBUDIDAYA IKAN DI KABUPATEN LEBONG MELALUI PENGEMBANGAN AGRIBISNIS IKAN SEPAT SIAM - Irnad Irnad; Reswita Reswita; Dewi Purnama (DHARMA RAFLESIA, 2018)
Sumber Rezeki Farmers Group and Maju Bersama Farmers Group are the farmers group existing at Tabeak Kauk village within 150 km from Bengkulu City. Sumber Rezeki Farmers Group and Maju Bersama Farmers Group were formed in 1999 with 20 members of each. One of the activities of farmer groups is fish farming. The most dominant fish cultivated by the farmers is the Goldfish, but a byproduct of farming Goldfish is Siamese Snakeskin fish. Siamese Snakeskin fish during this time include wild fish due to grow and multiply without cultivated by farmers. Snakeskin fish when cultivated intensively will provide enormous benefits for the economic development of members of farmer groups and villagers at Tabeak Kauk village, besides the easiness in the maintenance, the value of Siamese Snakeskin fish can be increased into dried fish. However, there are some problems faced by farmers' groups. The first problem is the limited availability of water to irrigate the pond. Contributing factor is the limited availability of water to irrigate their pool as a result having a lot of dead fish, there is even a farmer who can not do the fish farming until the rainy season comes because irrigation water was insufficient to irrigate their pool. The second problem is the high price of fish feed, the result are unoptimal fish growth and low production. The third problem is the problem of handling / processing after harvest. During this time, the fish is sold in fresh and is not accompanied processing activities, consequently the price of fish sold cheap, because if the fish was not immediately sold, those fish will rot. The fourth problem is the organization / group entrepreneurial for post-harvest processing of fish has not been there. Based on the problems faced, the purpose of this IbM activities are: 1) provide knowledge  transfer partners in  developing the cultivation of Siamese Snakeskin fish conjoined with a tarp, ranging from the spread of seeds, production management / maintenance, and harvesting, 2) provide knowledge transfer to farmers about how to manufacture Siamese Snakeskin fish feed, 3) increase the added value of fish production and farmers' income through diversification of products of Siamese Snakeskin fish into dried fresh and dried salted fish, 4) form an entrepreneurial group that has creativity and independent spirit. Methodology of Science and technology for the Community approach (IbM) will be delivered with extension and cultivation practices, feed manufacturing training, manufacture of dried fish training, and the formation of entrepreneurial  groups.  Results  of  IbM  activity  were  members  of  farmers  have  the knowledge and skills of fish farming intensively in pool tarp, feed manufacturing, increase the added value of the cultivation of fish, trigger creative spirit of farmers in creating refined products based food fish healthy and practical, as well as publications local and national scientific. Keywords: Siamese Snakeskin fish Farming, Post-Harvest Processing, IbM